BUDGETING IN RELATION TO STANDARD COSTS. - Blocker, J. G. (The Accounting Review, 1936)
The article discusses the role that budgets and a system of budgetary control play in the development and operation of standard costs. In fact, the statement can safely be made that budgeting must precede the accurate and effective determination of standard costs, at least as far as price standards of material, labor, and overhead are concerned, and conversely, a plan of budgetary control is much more successfully installed in concerns having standardized production processes and operating under standard-cost-accounting systems. Budgetary control and standard costs are inseparable and are each a necessary adjunct of managerial planning. Standard costs are estimated costs that are believed to represent ideal conditions to which it is hoped that actual costs may be made to conform. Standard costs are neither actual average, nor normal costs, but are estimates of what costs should be under as nearly perfect conditions as it is possible to secure. Standard costs may, therefore, be defined as representing a forecast of what costs should be under normal conditions, and as furnishing a basis for measuring productive efficiency.